2013
DOI: 10.1021/jp4024316
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Structural Investigation of Cs2CO3-Doped MgO Sorbent for CO2 Capture at Moderate Temperature

Abstract: MgO sorbents doped with alkali-metal carbonates have been shown to exhibit improved sorption capacities at both low and moderate operating temperatures, compared to pure MgO sorbents. However, the mechanism of how alkali-metal carbonates enhance the CO2 sorption is not well understood. Using in situ X-ray diffraction, TEM, and thermogravimetric analysis, we have shown that the cesium dopants in the Cs2CO3-doped MgO nanoparticle system do not simply act as a promoter in sorption of CO2, but rather as a reagent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 32 publications
7
52
0
Order By: Relevance
“…In recent years, many experiments regarding magnesium oxide (MgO) based material has been conducted, advantages in distinguish applications of MgO or magnesia has been also discovered [1][2][3][4][5][6]. A great number of applications such as refractory materials [4], catalyst [1,5,[7][8][9], carbon dioxide chemisorbents [6], reflecting and anti-reflecting coating [10], toxic waste remediation [11] and additive to heavy fuel oil [2] utilized MgO powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many experiments regarding magnesium oxide (MgO) based material has been conducted, advantages in distinguish applications of MgO or magnesia has been also discovered [1][2][3][4][5][6]. A great number of applications such as refractory materials [4], catalyst [1,5,[7][8][9], carbon dioxide chemisorbents [6], reflecting and anti-reflecting coating [10], toxic waste remediation [11] and additive to heavy fuel oil [2] utilized MgO powders.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of applications such as refractory materials [4], catalyst [1,5,[7][8][9], carbon dioxide chemisorbents [6], reflecting and anti-reflecting coating [10], toxic waste remediation [11] and additive to heavy fuel oil [2] utilized MgO powders. These applications requires different characteristic of MgO including the morphology of the particle [12].…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature sorbent technology has been studied extensively in order to decrease the CO 2 emission from flue gases of the power plant and industries as a post combustion process [1][2][3][4][5][6]. The system for carbon capture such as membrane, molecular sieves and unique solvents has been devised while these are expected to be high cost and energy demanding.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the sulphur oxide gases readily sorb onto the CO 2 sorbents and degrade the sorbent for further CO 2 sorption due to their strong affinity with the metal oxide sorbent.MgO phase mostly intact, similar to the one observed for carbonation10 .Therefore, this study is concerned with the tolerance of the proposed CdO-NaI and MgO-Cs 2 CO 3 composites towards the syngas constituents hydrogen, water, carbon dioxide and H 2 S. Screening tests by thermogravimetric analysis (TGA) were used to examine the temperature range of the…”
mentioning
confidence: 97%
“…sample to H 2 S. The original material contained MgO and a hydrated Cs 2 CO 3 phase if analysed by ex-situ powder XRD after heat treatment6,10 . After H 2 S treatment, MgO is still visible in the pattern.…”
mentioning
confidence: 99%